1979
DOI: 10.1002/jcp.1041000106
|View full text |Cite
|
Sign up to set email alerts
|

Tuftsin‐macrophage interaction: Specific binding and augmentation of phagocytosis

Abstract: The binding of [3H]tuftsin to normal and in vivo stimulated mouse peritoneal macrophage populations was studied at 22 degrees C. The [3H]tuftsin binding to thioglycollate-stimulated macrophages was shown to be rapid and saturable, with an equilibrium dissociation constant (K(D)) (calculated from a Scatchard plot) of 5.3 X 10(-8) M. The calculated number of binding sites per macrophage amounts to approximately 72,000. Binding competition studies with unlabelled tuftsin yielded a K(D) of 5.0 X 10(-8) M. [3H] [N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…It is worth noting also that other hypothalamic neuropeptides may be involved in the neural modulation of the local immune and hypersensitivity reaction [22]. Recent findings from our laboratory as well as others have shown that human monocytes are attracted towards physiologi cal concentrations of a number of neuropeptides including corticoliberin [24], substance P [ 16] and neurotensin [3]. In sum mary, these studies have provided addition support for an in volvement of GHRH in the bidirectional interaction between neuroendocrine and immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting also that other hypothalamic neuropeptides may be involved in the neural modulation of the local immune and hypersensitivity reaction [22]. Recent findings from our laboratory as well as others have shown that human monocytes are attracted towards physiologi cal concentrations of a number of neuropeptides including corticoliberin [24], substance P [ 16] and neurotensin [3]. In sum mary, these studies have provided addition support for an in volvement of GHRH in the bidirectional interaction between neuroendocrine and immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone induces T cell proliferation [ 13] and production of superoxide anions by macrophages [14], whereas thyrotropin (TSH) enhances the production of antibodies [15]. In parallel, immune cells are able to express receptors for those hormones, as for instance ACTH [16], (I-endorphin [17], growth hormone, prolactin [18], but also for other neuroendocrine peptides as vasoactive intestinal polypeptide (VIP) [19], neurotensin [20], somatostatin or substance P [21],…”
Section: Neuroendocrine Systems and Immune Responsesmentioning
confidence: 99%
“…Accumulating evi dence indicates that neuroendocrine mechanisms can modulate this activation process [Payan and Goetzl, 1985;Wybran, 1985;Blalock and Smith, 1985;Nordlind and Mutt, 1986a, b]. Hence, studies both in vitro and in vivo, have shown that various neuropeptides influence reactions such as B lymphocyte prolifera tion and antibody synthesis, T lymphocyte prolifera tion, natural killer cell and macrophage activity as well as lymphocyte migration [Johnson et al, 1982;Bar-Shavit et al, 1982;Payan et al, 1983;Mathews et al, 1983;Ottaway, 1984;Nordlind and Mutt, 1986a, b;Sandberg and Ljungdahl, 1986]. Neuropeptides have been found in tissues where immune reactions are initiated such as the skin, gut and respiratory tract [Felten et al, 1985], Thus, in these tissues, which often are considered as primary sites of antigenic exposure, neuropeptides might be involved in the regulation of lymphocyte activation.…”
Section: Introductionmentioning
confidence: 99%